The Dubious Enhancement: Making South Korea a Plastic Surgery Nation. Issue 1 (1st March 2016) - Leem, So Yeon
Abstract : This study investigates the widely recognizable discourse that characterizes South Korea as a plastic surgery nation by tracing media coverage of plastic surgery as published in two major Korean newspapers from 1960 to 2009.This study attempts to enrich our understanding of plastic surgery in modern times within the Korean context by delineating three distinctive periods of plastic surgery: legitimization (1960–79), popularization (1980–99), and industrialization (2000s). I show how the discourse of South Korea as a plastic surgery nation is both a local and a global construction. This paper further aims to deepen our understanding of enhancement technology by showing how the plastic surgery discourse in South Korea demonstrates the permeability of the boundaries between therapy and enhancement, bodily and social enhancement, and the individual and collective body. While the discourse has reinforced these complementary and intertwined relationships, what enhancement means for whom has not been questioned. I argue that statistics have variously been used to proclaim the ubiquity of plastic surgery, which works to "make up people" without attending to the actual experiences and effects of plastic surgery, either for individuals or the nation. In this way, the characterization of South Korea as a plastic surgery nation is a dubious construction.